La percezione del paesaggio nella lettura dell’interfaccia tra città e porto: il caso di Marsiglia - Bertoni, Angelo (Ri-Vista. Research for landscape architecture, 2017)
The transformations of many port cities on the shores of the Mediterranean Sea produced the construction of new urban landscapes through the conversion of disused areas into new neighbourhoods for tertiary activity, residence or leisure, but only recently the notions of landscape and sustainability have become part of the framework of analysis and design of the contact areas between the city and the port. The case of Marseilles is exemplary in this respect. After a review of the history of the city’s coastal layout in the north of the old port since the mid-1990s, the essay offers a landscape reading of the city-port interface with attention to three spatial sequences: the area between the new museums and the historic neighbourhood Panier; one of the accesses to the port in relation to the urban context and transport infrastructures; the coastal line of Etaque, where a new dialogue between the built-up area and the sea was recreated. The landscape cognitive system can contribute to a new reading of the coastline between the city and the port of Marseilles and promote designs more respectful of the social and environmental sustainability criteria.